Septo-temporal distribution and lineage progression of hippocampal neurogenesis in a primate (Callithrix jacchus) in comparison to mice - Amrein, Irmgard; Nosswitz, Michael; Slomianka, Lutz; van Dijk, R. Maarten; Engler, Stefanie; Klaus, Fabienne; Raineteau, Olivier; Azim, Kasum (Frontiers in Neuroanatomy, 2015)
Adult born neurons in the hippocampus show species-specific differences in their numbers, the pace of their maturation and their spatial distribution. Here, we present quantitative data on adult hippocampal neurogenesis in a New World primate, the common marmoset (Callithrix jacchus) that demonstrate parts of the lineage progression and age-related changes. Proliferation was largely (~70%) restricted to stem cells or early progenitor cells, whilst the remainder of the cycling pool could be assigned almost exclusively to Tbr2+, intermediate precursor cells in both neonate and adult animals (20-122 months). Proliferating DCX+ neuroblasts were virtually absent in adults, although rare MCM2+/DCX+ co-expression reveals a small, persisting proliferative potential. Co-expression of DCX with calretinin was very limited in marmosets, suggesting that these markers label distinct maturational stages. In adult marmosets, numbers of MCM2+, Ki67+, and significantly Tbr2+, DCX+ and CR+ cells declined with age. The distributions of granule cells, proliferating cells and DCX+ young neurons along the hippocampal longitudinal axis were equal in marmosets and mice. In both species, a gradient along the hippocampal septo-temporal axis was apparent for DCX+ and resident granule cells. Both cell numbers are higher septally than temporally, whilst proliferating cells were evenly distributed along this axis. Relative to resident granule cells however, the ratio of proliferating cells and DCX+ neurons remained constant in the septal, middle and temporal hippocampus. In marmosets, the extended phase of the maturation of young neurons that characterizes primate hippocampal neurogenesis was due to the extension in a large CR+/DCX- cell population. This clear dissociation between DCX+ and CR+ young neurons has not been reported for other species and may therefore represent a key primate specific feature of adult hippocampal neurogenesis.